Recent update in ultrasound contrast agents - Vohra, Poonam; Jasuja, Kusum (International Journal of Scientific Reports, 2016)
Contrast-enhanced ultrasound (CEUS) is the application of ultrasound contrast medium to traditional medical sonography. Ultrasound contrast agents rely on the different ways in which sound waves are reflected from interfaces between substances. This may be the surface of a small air bubble or a more complex structure. Commercially available contrast media are gas-filled microbubbles that are administered intravenously to the systemic circulation. Microbubbles have a high degree of echogenicity (the ability of an object to reflect ultrasound waves). There is a great difference in echogenicity between the gas in the microbubbles and the soft tissue surroundings of the body. Thus, ultrasonic imaging using microbubble contrast agents enhances the ultrasound backscatter, (reflection) of the ultrasound waves, to produce a sonogram with increased contrast due to the high echogenicity difference. CEUS can be used to image blood perfusion in organs, measure blood flow rate in the heart and other organs, and for other applications.